1997
DOI: 10.1126/science.278.5341.1270
|View full text |Cite
|
Sign up to set email alerts
|

Belated Decision in the Hilbert-Einstein Priority Dispute

Abstract: According to the commonly accepted view, David Hilbert completed the general theory of relativity at least 5 days before Albert Einstein submitted his conclusive paper on this theory on 25 November 1915. Hilbert's article, bearing the date of submission 20 November 1915 but published only on 31 March 1916, presents a generally covariant theory of gravitation, including field equations essentially equivalent to those in Einstein's paper. A close analysis of archival material reveals that Hilbert did not anticip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
76
0
3

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(79 citation statements)
references
References 5 publications
0
76
0
3
Order By: Relevance
“…13 Page proofs of Hilbert's paper, which was not published until March 1916, surfaced in the late 1990s. An analysis of them 14 shows that Einstein need not have worried about Hilbert in November 1915. In important ways, the theory presented in the page proofs is closer to the Entwurf theory than to general relativity in its final form.…”
Section: Coordinate Restrictionsmentioning
confidence: 99%
“…13 Page proofs of Hilbert's paper, which was not published until March 1916, surfaced in the late 1990s. An analysis of them 14 shows that Einstein need not have worried about Hilbert in November 1915. In important ways, the theory presented in the page proofs is closer to the Entwurf theory than to general relativity in its final form.…”
Section: Coordinate Restrictionsmentioning
confidence: 99%
“…Although it would not be inappropriate to 4 David Hilbert submitted his paper on these field equations five days before Einstein, though it was published only on March 31, 1916. Recent analysis [17] of archival materials has revealed that Hilbert made significant changes in the proofs. The originally submitted version of his paper contained the theory which is not generally covariant, and the paper did not include equations (III).…”
Section: Einstein's Field Equationsmentioning
confidence: 99%
“…Now when a slightly nonspherical star starts to collapse, the perturbations become dynamical and propagate as waves. Their evolution can be determined by solving the wave equation (17). Because of the potential barrier (18) the waves get backscattered and produce slowly decaying radiative tails, as shown in the classical papers by Price [108,109], and generalized to the Reissner-Nordström case in [107,110].…”
Section: Reissner-nordström Black Holes and The Question Of Cosmic Cementioning
confidence: 99%
See 1 more Smart Citation
“…Einstein. In 1997 an article appeared in the journal "Science" under the title "Belated Decision in the Hilbert-Einstein Priority Dispute" [2], the authors of which claim that "...knowledge of Einstein's result may have been crucial to Hilbert's introduction of the trace term into his field equations". On this ground they push forward their point of view "that radically differs from the standard point of view" and which is exposed in a many-page ref.…”
Section: Introductionmentioning
confidence: 99%